Prostate-specific antigen testing accuracy in community practice - Adams-Cameron Meg; Gilliland Frank D; Hoffman Richard M; Hunt William C; Key Charles R (BMC Family Practice, 2002)
Abstract Background Most data on prostate-specific antigen (PSA) testing come from urologic cohorts comprised of volunteers for screening programs. We evaluated the diagnostic accuracy of PSA testing for detecting prostate cancer in community practice. Methods PSA testing results were compared with a reference standard of prostate biopsy. Subjects were 2,620 men 40 years and older undergoing (PSA) testing and biopsy from 1/1/95 through 12/31/98 in the Albuquerque, New Mexico metropolitan area. Diagnostic measures included the area under the receiver-operating characteristic curve, sensitivity, specificity, and likelihood ratios. Results Cancer was detected in 930 subjects (35%). The area under the ROC curve was 0.67 and the PSA cutpoint of 4 ng/ml had a sensitivity of 86% and a specificity of 33%. The likelihood ratio for a positive test (LR+) was 1.28 and 0.42 for a negative test (LR-). PSA testing was most sensitive (90%) but least specific (27%) in older men. Age-specific reference ranges improved specificity in older men (49%) but decreased sensitivity (70%), with an LR+ of 1.38. Lowering the PSA cutpoint to 2 ng/ml resulted in a sensitivity of 95%, a specificity of 20%, and an LR+ of 1.19. Conclusions PSA testing had fair discriminating power for detecting prostate cancer in community practice. The PSA cutpoint of 4 ng/ml was sensitive but relatively non-specific and associated likelihood ratios only moderately revised probabilities for cancer. Using age-specific reference ranges and a PSA cutpoint below 4 ng/ml improved test specificity and sensitivity, respectively, but did not improve the overall accuracy of PSA testing.